Rekomendasi Pemilihan Minat Studi Menggunakan Metode Mamdani Studi Kasus : Program Studi Sistem Informasi FTI UMBY - Anief Fauzan Rozi; Agus Sidiq Purnomo (Faculty of Computer Science, University of Jember, 2017)
Determination of the concentration / interest of study for most students can’t be applied easily. Most students still do not know exactly what their concentration is. Only for students who are smart in IPK and mature in the pattern of thinking that can determine the concentration of studies easily and not wrong target. Besides still confused and tend to choose the concentration that is not in accordance with the interests and talents of each. Confusion or the majority of students' mistakes to specialization in accordance with the ability due to the number of elective courses offered in line with the interests offered. Based on this problem, it takes a decision making tool or recommendation to the student about the concentration/interest of study whether the most appropriate according to ability. In this research will be made decision support system for recommendation of study by implementing fuzzy inference (mamdani). Where this system will provide information on the interest of the study can be selected based on the value variable. So it can help students in choosing the interests of the study in accordance with the appropriate competence and interest talent. Based on the 20 data that have been tested, obtained 19 data and 1 data that is not appropriate, thus can be calculated the performance of the system that is equal to 95%.